(untitled) (JOURNAL OF ADVANCES IN AGRICULTURE, 2015)
Field studies on efficacy of different insecticides against the diamondback moth, Plutella xylostella L. and their toxicity to parasitoid,Cotesia plutellae on cauliflower crop were carried out on farmers fields. The insecticides tested were abamectin, emamectin benzoate, lufenuran, spinosad, endosulfan, profenophos, and a mixture of endosulfan +lufenuran. The pretreatment observation was taken 24 hrs before and post treatment observations were recorded 48, 72 and 96 hrs, 7 and 15 days after application of insecticides. On overall basiss abamectin and emamectin benzoate were found to be the most effective insecticides against Plutella xylostella, followed by profenophos and lufenuron with P. xylostella population of 1.75, 2.12, 3.69, and 4.12 insects per plant, respectively. While, spinosad and lufenuron were found comparatively less toxic to parasitoid, C. plutellae, followed by endosulfan with parasitism of 36.74, 36.72 and 35.65%, respectively. Whereas, abamectin was highly toxic to C. plutellae, with parasitism of 19.83% only.